Resenha do livro "Nazi Germany and the Jews, 1933-1945" - Funari, Pedro Paulo Abreu (Revista Eletrônica História em Reflexão, 2012)
FRIEDLÄNDER, Saul. Nazi Germany and the Jews, 1933-1945. Nova Iorque: Harper, 2009.